PENGELOLAAN BRANDING PERUSAHAAN DI MEDIA SOSIAL MELALUI PENDEKATAN CONTENT MARKETING - Falaah Saputra Siregar; Hadi Purnama; Slamet Parsono (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
As a newly established company, Etapasbar is aiming to further increasing their brand awareness and branding to customers and Pasar Baru Bandung Merchant. Etapasbar chose to use instagram @etalasepasarbaru as the main social media to communicate with the audience. This research is done to find out how do Etapasbar manage company branding by using content marketing approach in Instagram based on case study of Bahenol, Balantik, and Beja ti Pasbar. Bahenol, Balantik, and Beja ti Pasbar are three main content programs created for fulfilling the need of brand awareness and branding. This research object is the strategic and management of branding in Etapasbar. Data is collected by using interview and observation. Researcher will analyze the three main content programs based on observation then researcher will ask for futher indepth information of the programs. Discussion will be breakdown into three section, flow and strategic management of content, effort of increasing brand awreness, and building branding. This research resulting in the strategic formulation that is used by Etapasbar based on market segmentation, the attempt of increasing brand awareness is done by using attribute that is shown in the content in Instagram, Etapasbar branding is created and formed by satisfaction of customer and registered merchant at Etapasbar. Keywords: content marketing, corporate branding, erapasbar, social media